Pengelolaan Dana Desa Untuk Good Governance Di Desabiji Nangka Kecamatan Sinjai Borong Kabupaten Sinjai - Kamal, Ahmad; Muhammadiah, Muhammadiah; Fatmawati, Fatmawati (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
ABSTRACTThe purpose of this study was to find out the implementation and factors  through the Village Innovation Exchange in Sinjai Borong District, Sinjai Regency. This study used phenomenology with qualitative research type. The number of research informants was 8 people. Research information was collected through observation, interviews and documentation. Based on the results of research on Reinventing Government through the Village Innovation Exchange in Sinjai Borong District, Sinjai Regency on the principle of catalytic government (Catalytic Government) showed that there were efforts to improve the welfare of rural communities by providing a platform or program that could initiate village businesses in utilizing village funds they had by innovative way. The principle of government owned by the community showed that the community gained knowledge on the basis of their own initiative and the potential of the village so that they Could get additional income. The inhibiting factor was the lack of follow-up from the community after the implementation of the Village Innovation Exchange activities and the existence of differences of opinion regarding village innovation activities.Keywords: Village fund management, good governance